2019
DOI: 10.3390/ijms20194896
|View full text |Cite
|
Sign up to set email alerts
|

Progress in iPSC-Based Modeling of Psychiatric Disorders

Abstract: Progress in iPSC-based cellular systems provides new insights into human brain development and early neurodevelopmental deviations in psychiatric disorders. Among these, studies on schizophrenia (SCZ) take a prominent role owing to its high heritability and multifarious evidence that it evolves from a genetically induced vulnerability in brain development. Recent iPSC studies on patients with SCZ indicate that functional impairments of neural progenitor cells (NPCs) in monolayer culture extend to brain organoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 66 publications
(108 reference statements)
1
34
0
Order By: Relevance
“…Synaptic connections formed within this microfluidic system as evidenced by a rabies virus tracing assay. Moreover, multi-electrode array (MEA) recordings and whole-cell patch clamp techniques showed that the SCZ hCA3 neurons were impaired in both spontaneous and evoked electrophysiological activity (see also [63]).…”
Section: Outlook and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synaptic connections formed within this microfluidic system as evidenced by a rabies virus tracing assay. Moreover, multi-electrode array (MEA) recordings and whole-cell patch clamp techniques showed that the SCZ hCA3 neurons were impaired in both spontaneous and evoked electrophysiological activity (see also [63]).…”
Section: Outlook and Discussionmentioning
confidence: 99%
“…Beyond in vitro studies, transplanting of human brain organoids into mouse brains was recently performed to establish an in vivo model of human brain neuronal connectivity [111]. Human brain organoids underwent vascularization and integration with microglia, extended long-range axons, and exhibited synchronized neural activity and functional connectivity within the mouse brain (see also [63]). In a nutshell, human brain organoid in vitro and in vivo systems open up multiple opportunities to investigate causal mechanisms and genes on cellular phenotypes lying at the heart of psychiatric disorders.…”
Section: Outlook and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, proteomics using induced pluripotent stem cells (iPSC)-derived neurons and microglia from individuals with TS and related disorders will continue to push the field toward better understanding of disease pathophysiology which hopefully will contribute to the future development of therapeutics against specific targets (204,205).…”
Section: Insight From Animal Models (Table 3)mentioning
confidence: 99%
“…The use of iPSC-based models for the latter disease type is more problematic with respect to monogenic diseases, since the phenotype is often the result of multiple small-effect genetic variants in combination with environmental factors. However, this approach was used to model many different complex diseases including Alzheimer’s disease, Parkinson’s disease, schizophrenia, and cardiac arrhythmias [ 132 , 133 , 134 , 135 ]. Without knowing the detailed underlying genetics, differentiated patient-specific iPSCs could provide disease-relevant cells that carry all the genetic elements implicated in the development of the disease and can be useful to analyze the common mechanisms of disease development.…”
Section: Ipscsmentioning
confidence: 99%